Effect of Activation Mode on Flexural Strength and Elasticity Modulus of Dual Cure Resin Cements - Guimaraes DDS, MSc, PhD, Isadora; Murillo DDS, MSc, Fabian; De Goes DDS, MSc, PhD, Mario (Odovtos - International Journal of Dental Sciences, 2016)
Objective: This study evaluated the effect of the activation mode on flexural strength and elasticity modulus of four dual cure resin-based cements. Methods: Two self-adhesive resin cements (Clearfil SA Cement (CSA) and RelyX U100 (U)) and two conventional resin cements (Clearfil Esthetic Cement (CE)and RelyX ARC (ARC)) were used to produce a total of 45 bar specimens (7x2x2 mm) using three different activation modes (n=15): Direct light-cure (D), Indirect light-cure using a 2mm composite resin barrier (I) and Self-cure (S). Three-point flexural tests were performed after 24 hours water storage at 37° C, using a universal testing machine (Instron) at a cross-speed of 0.5 mm/min until fracture. Flexural strength (MPa) and elasticity modulus values were subjected to ANOVA and Tukey’s Test (=0.05). Results: Data revealed that light polymerized groups presented statistically higher flexural strength (CSA/D=113.63 ± 19.65; CSA/I=80.66 ± 23.74; U/D=101.33 ± 9.8; U/I=94.96 ± 36.9; CE/D=219.08 ± 39.94; CE/I=226.42 ± 34.59; ARC/D=150.03 ± 26.15; ARC/I=111.78 ± 14.28) and also elasticity modulus values (CSA/D = 2.9 ± 0.6; CSA/I = 1.5 ± 0.4; U/D = 2.9 ± 0.5; U/I = 2.6 ± 1.4; CE/D = 6.5 ± 1.3; CE/I = 5.8 ± 1.0; ARC/D = 4.2 ± 0.93; ARC/I = 2.5 ± 0.5) compared to self-cured groups (flexural strength: CSA/S=65.81 ± 21.84; U/S=53.62 ± 28.73; CE/S=129.02 ± 51.67; ARC/S=77.98 ±19.61 and elasticity modulus: CSA/S = 1.4 ± 0.5; U/S = 1.2 ± 0.7; CE/S = 2.2 ± 1.5; ARC/S = 1.0 ± 0.5). The usage of a composite resin barrier only affected the mechanical properties of ARC and CSA. Conventional resin cements presented higher flexural strength values than the self-adhesive cements. CE presented the highest values compared to all other cements. No statistical difference was observed between self-adhesive cements. Conclusion: Light-curing of resin luting cements produced higher flexural strength for all tested materials. Similar mechanical behavior was observed for the tested self-adhesive cements.